Antibiotic prophylaxis for tube thoracostomy placement in trauma: a practice management guideline from the Eastern Association for the Surgery of Trauma. Issue 1 (25th October 2022) - Freeman, Jennifer J; Asfaw, Sofya H; Vatsaas, Cory J; Yorkgitis, Brian K; Haines, Krista L; Burns, J Bracken; Kim, Dennis; Loomis, Erica A; Kerwin, Andy J; McDonald, Amy; Agarwal,, Suresh; Fox, Nicole; et al.
Abstract : Background: Antibiotic prophylaxis is routinely administered for most operative procedures, but their utility for certain bedside procedures remains controversial. We performed a systematic review and meta-analysis and developed evidence-based recommendations on whether trauma patients receiving tube thoracostomy (TT) for traumatic hemothorax or pneumothorax should receive antibiotic prophylaxis. Methods: Published literature was searched through MEDLINE (via PubMed), Embase (via Elsevier), Cochrane Central Register of Controlled Trials (via Wiley), Web of Science and ClinicalTrials.gov databases by a professional librarian. The date ranges for our literature search were January 1900 to March 2020. A systematic review and meta-analysis of currently available evidence were performed using the Grading of Recommendations Assessment, Development and Evaluation methodology. Results: Fourteen relevant studies were identified and analyzed. All but one were prospective, with eight being prospective randomized control studies. Antibiotic prophylaxis protocols ranged from a single dose at insertion to 48 hours post-TT removal. The pooled data showed that patients who received antibiotic prophylaxis were significantly less likely to develop empyema (OR 0.47, 95% CI 0.25 to 0.86, p=0.01). The benefit was greater in patients with penetrating injuries (penetrating OR 0.25, 95% CI 0.10 to 0.59, p=0.002, vs blunt OR 0.25, 95% CI 0.06 to 1.12, p=0.07). Administration of antibiotic prophylaxis did not significantly affect pneumonia incidence or mortality. Discussion: In adult trauma patients who require TT insertion, we conditionally recommend antibiotic prophylaxis be given at the time of insertion to reduce incidence of empyema. PROSPERO registration number: CRD42018088759.